2010
DOI: 10.1073/pnas.1008469107
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of the nucleolinus, a dynamic RNA-rich organelle associated with the nucleolus, spindle, and centrosomes

Abstract: The nucleolinus is an RNA-rich compartment, closely apposed to or embedded within the nucleolus. Discovered over 150 y ago, fewer than two dozen articles have been published on the nucleolinus, probably because complex histochemical stains are required for its visualization in the great majority of cells. The nucleolinus has been reported in invertebrate oocytes, mammalian and amphibian epithelial cells, neurons, and several transformed cell lines. A prominent nucleolinus, clearly visible with transmitted ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…At least fifteen distinct molecules for which the full length sequences are known have been localized to the centrosome by in situ hybridization in four laboratories (Lambert and Nagy, 2004;Alliegro et al, 2006;Alliegro and Alliegro, 2008;Kingsley et al, 2007;Lecuyer et al, 2007). Others have been localized to the spindle (Groismann et al, 2000;Lecuyer et al, 2007;Alliegro et al, 2010) and dozens more are either presumed (by biochemical enrichment) or known (by in situ localization based on partial sequences) to be present in these structures (Lecuyer et al, 2007;Alliegro and Alliegro, 2008). We may now return our attention to the function and origin of spindle and centrosomal RNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least fifteen distinct molecules for which the full length sequences are known have been localized to the centrosome by in situ hybridization in four laboratories (Lambert and Nagy, 2004;Alliegro et al, 2006;Alliegro and Alliegro, 2008;Kingsley et al, 2007;Lecuyer et al, 2007). Others have been localized to the spindle (Groismann et al, 2000;Lecuyer et al, 2007;Alliegro et al, 2010) and dozens more are either presumed (by biochemical enrichment) or known (by in situ localization based on partial sequences) to be present in these structures (Lecuyer et al, 2007;Alliegro and Alliegro, 2008). We may now return our attention to the function and origin of spindle and centrosomal RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Three other studies have found specific RNAs associated with the centrosomes and/or spindle in surf clam (Spisula solidissima) oocytes (Alliegro et al, 2006;Alliegro and Alliegro, 2008;Alliegro et al, 2010). The first two reports described a set of RNAs that are significantly enriched in isolated centrosomes and includes confirmatory in situ hybridizations for four of these.…”
Section: Findings Of Specific Nucleic Acids Associated With the Centrmentioning
confidence: 99%
“…These include cilia and flagella, the basal bodies from which they arise (themselves derived from centrioles), and the mitotic spindle. There is evidence to suggest that certain intranuclear structures may be considered part of this system as well (Allen 1951(Allen , 1953Tanaka 1973;Laane and Haugli 1974;Alliegro et al 2010Alliegro et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, the observation that a component of a unitary microtubule-based motility organelle could nucleate microtubules is no revelation. The karyomastigont perspective also addresses reports of MTOC components in the nucleus of some cells (Tanaka 1973;Laane and Haugli 1974;Alliegro et al 2010Alliegro et al , 2012. Viewed in light of the unitary karyomastigont, the relationship between the microtubule-based motility system and the nucleus is not simply one devised to segregate genetic material, but a much more integrated, reciprocal relationship with shared and exchanged elements.…”
mentioning
confidence: 99%
“…The nucleolinus (NLi) 2 is a compartment or organelle described in a wide variety of cells and with a long although virtually forgotten history (2,3). In cells where it is clearly visible, it is closely apposed to the nucleolus, and in other cells where it has been described it appears to be integrated within the nucleolus.…”
mentioning
confidence: 99%